The chronological, sedimentary and environmental context for the archaeological deposits at Blombos Cave, South Africa. (1st May 2020) - Jacobs, Zenobia; Jones, Brian G.; Cawthra, Hayley C.; Henshilwood, Christopher S.; Roberts, Richard G.
Abstract: The site of Blombos Cave (BBC) is well known for archaeological remains that have advanced our understanding of the development of modern human behaviour during the Middle Stone Age (MSA). Occupation of the cave occurred against a backdrop of landscape-scale environmental and sedimentary processes that provide the broader context for finer-scale interpretations of the site-formation history and archaeological patterns detected in the cave deposits. Aeolian and palaeosol sequences are abundant in the vicinity of BBC and these provide a partial view of the past landscapes available to the inhabitants of the cave. An important extension to the palaeo-landscape around BBC currently lies submerged on the Agulhas Bank, as sea levels were lower than at present for the entire period of human occupation of BBC. In this paper, we revisit the optically stimulated luminescence (OSL) chronology for the full sequence of sediment deposition inside BBC, increasing the number of dated samples to a total of 40 and revising the period of MSA occupation to between 97.7 ± 7.6 and 71.0 ± 5.7 ka (uncertainties at 95.4% probability). We describe the geological successions at four main areas around BBC, estimate the time of sediment deposition using OSL, and describe and interpret three seismic profiles on the Agulhas Bank, offshore of BBC. By correlating these onshore and offshore geological sequences with the sedimentary deposits inside BBC, we place the archaeological record within a landscape-scale chrono-stratigraphic framework to examine how environmental changes may have regulated the presence or absence of humans in the cave and surrounding terrain between about 100 and 70 ka. Highlights: We report new single-grain OSL ages for MSA layers at Blombos Cave, South Africa. We describe and date the geological successions around Blombos Cave. We describe and interpret seismic profiles on the Agulhas Bank, offshore of the cave. We correlate the onshore and offshore geological sequences with the cave sediments. We examine how environmental changes regulated human occupation of Blombos Cave.